Effect of Lime (Citrus aurantifolia) Concentration and Stirring Time on the Quality of Palm Oil-Based Margarine - N Narsih; Indrastuti, Y. Erning; Safitri, Sela; Pratama, Borneo Satria (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to analyze the effects of lime (Citrus aurantifolia) concentration and stirring time on the quality of palm oil-based margarine. The treatments included lime concentrations of 1%, 2%, and 3%, with stirring times of 5 minutes and 10 minutes. The observed parameters included moisture content, fat content, free fatty acid levels, emulsion stability, spread ability, color, texture, aroma, and taste. Analysis of variance (ANOVA) results indicated that lime concentration and stirring time significantly influenced most margarine quality parameters. Increasing lime concentration and stirring time resulted in a rise in moisture content, ranging from 1.7249% to 3.1094%, and an increase in free fatty acid levels from 0.2543% to 0.4195%. Conversely, fat content decreased, ranging from 88.4387% to 81.3954%. Emulsion stability was within 99.6927%–99.8795%, while spread ability varied from 2.6335 g/mm² to 3.6473 g/mm². In terms of organoleptic properties, margarine color showed significant differences, with the highest value of 3.0000 (yellow) observed in the 3% lime concentration with a 5-minute stirring time, and the lowest value of 1.9524 (very yellow) found in the 2% lime concentration with a 10-minute stirring time. Margarine texture varied from firm to slightly firm, with the highest score of 2.6667 recorded for the 1% lime concentration with both 5- and 10-minute stirring times. Aroma intensity increased with higher lime concentrations, with the strongest aroma recorded at 2.9524 in the 3% lime treatment with a 5-minute stirring time. Meanwhile, taste remained mostly neutral, with the highest score of 3.3333 observed in the 2% lime concentration with a 10-minute stirring time. This study highlights that the appropriate combination of lime concentration and stirring time can produce margarine with improved quality characteristics